Implementation of a structured paediatric admission record for district hospitals in Kenya - results of a pilot study - Ogutu Bernhards; Esamai Fabian; Were Fred; Wasunna Aggrey; Wamae Annah; Mwakyusa Sekela; Muriithi Assumpta; Peshu Norbert; English Mike (BMC, 2006)
Abstract Background The structured admission form is an apparently simple measure to improve data quality. Poor motivation, lack of supervision, lack of resources and other factors are conceivably major barriers to their successful use in a Kenyan public hospital setting. Here we have examined the feasibility and acceptability of a structured paediatric admission record (PAR) for district hospitals as a means of improving documentation of illness. Methods The PAR was primarily based on symptoms and signs included in the Integrated Management of Childhood Illness (IMCI) diagnostic algorithms. It was introduced with a three-hour training session, repeated subsequently for those absent, aiming for complete coverage of admitting clinical staff. Data from consecutive records before (n = 163) and from a 60% random sample of dates after intervention (n = 705) were then collected to evaluate record quality. The post-intervention period was further divided into four 2-month blocks by open, feedback meetings for hospital staff on the uptake and completeness of the PAR. Results The frequency of use of the PAR increased from 50% in the first 2 months to 84% in the final 2 months, although there was significant variation in use among clinicians. The quality of documentation also improved considerably over time. For example documentation of skin turgor in cases of diarrhoea improved from 2% pre-intervention to 83% in the final 2 months of observation. Even in the area of preventive care documentation of immunization status improved from 1% of children before intervention to 21% in the final 2 months. Conclusion The PAR was well accepted by most clinicians and greatly improved documentation of features recommended by IMCI for identifying and classifying severity of common diseases. The PAR could provide a useful platform for implementing standard referral care treatment guidelines.